Using hypnosis in coaching psychology practice to enhance performance, reduce anxiety and increase self-efficacy - Palmer, S. (Coaching Psykologi, 2019)
Traditionally, hypnosis techniques have been applied within hypnotherapy and psychotherapy as a therapeutic intervention. This paper focuses on using hypnosis as a technique to enhance performance, reduce anxiety and increase self-efficacy in coaching and coaching psychology settings. A hypnosis script is included that can be adapted by practitioners to tackle presenting performance-related problems. Keywords: Hypnosis, coaching, coaching psychology, sport psychology, special state theory, non-state theory, self-efficacy, performance